Using integrated remote sensing methods in the Nagyerdő Natura 2000 area - Bozsik, Éva; Fórián, Tünde; Deák, Balázs; Riczu, Péter; Fehér, János; Heilmeier, Herman; Tamás, János (Acta Agraria Debreceniensis, 2014)
The more widely use of GIS, remote sensing technology provides appropriate data acquisition and data processing tools to build several national and international biodiversity monitoring system of environmental protection and natur conservation. The ChangeHabitats 2 is a similar international project, which uses airborne hyperspectral and airborne laser scanning (airborne LiDAR) sources beyond traditional data collection methods to build a monitoring system of Natura 2000 habitats. The goal of our research, on one hand, was to separate the most typical species of trees which can be found in the largest coverage in the research plots of Debreceni Nagyerdő Nature Reserve from field and airborne remote sensing data, use image classification that based on spectral and geometry (height) characteristics of the trees. On the other hand our goal was to evaluate the efficient use of the integration of mobilGIS, airborne hyperspectral and airborne LiDAR data collecting methods to complement or substitut of the traditional, field data collecting methods. We used ArcGIS 10.2 and Exelis 5.0 GIS software for data evaluation, in which the mosaicing, the selection of plots and the spectral image processing were carried out.